The analysis of teacher’s perception of the integration of Kasepuhan local wisdom into school curriculum - Khusyairin; Saud, Udin Syaefudin; Sururi; Hartini, Nani (Universitas Jambi, Indonesia, 2025)
The purpose of this study is to analyze teachers' perceptions of the integration of the Kasepuhan local wisdom into school curricula. Using a survey method, data were collected through questionnaires distributed to schoolteachers to evaluate their knowledge of the Kasepuhan cultural values, the extent of integrating these values into teaching practices, and the challenges encountered in implementing local wisdom-based education. The study also examined curriculum development, assessments, teacher competence, teaching materials, learning media, and community involvement. The results revealed that while 35% of teachers know Kasepuhan values, only 13.33% believe these values are applied in schools. A significant number (40%) indicated the need for curriculum adjustments to reflect local culture better, while 70% reported that local wisdom-based assessment criteria had not been optimally implemented. Furthermore, the study concludes that although teachers recognize the importance of integrating Kasepuhan wisdom, challenges such as insufficient resources, lack of training, and limited school facilities hinder its implementation.